(untitled) (Педагогіка вищої та середньої школи, 2022)
This article deals with the questtion about the youth clubs in out of school education and upbringing teenagers. With the help of the work o f youth cluds there is one more possibility of development pupils abilities, including them info the system of recearching and creative activity.